Education Needs to Support Architecture, Engineering, and Construction Collaboration Using Building Information Modeling - Rostam, Dilan M. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2019)
Projects in the construction industry involve multidisciplinary collaboration between the disciplines of architecture, engineering, and construction (AEC), and others. Conventionally, the collaboration between these disciplines relied on the recurrent exchange of relevant drawings and documents. Building information modeling (BIM) as a model-based process has given AEC professionals the tools to more efficiently plan, design, construct, and manage buildings and infrastructure. Yet the AEC industry has been reluctant in fully adopting the BIM as a single standard. This study explores and identifies the bottlenecks in adopting BIM as a single product lifecycle standard in the construction industry and advise on educating new engineers to become the generation to use a virtual collaborative working space covering the entire building lifecycle. Two conducted surveys targeting the AEC academia and industry revealed the needs for multilevel cross-disciplinary interactive collaborative BIM process modeling, and skilled workforce to increase the graduates’ marketability and BIM adaptability. It is concluded that the new age collaborative culture requires new generation of AEC players that are enabled to work on a shared virtual product model supported by proactive BIM skills learned through undergraduate programs.